Pelatihan Olimpiade Matematika Kepada Perwakilan Peserta Kegiatan Olimpiade Sains Nasional (OSN) - Iltavia, Iltavia; Fitri, Haida; Rahmi Safitri, Yolanda; Muhammad Yusuf; Desi Rahmadani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This training activity aims to provide enthusiasm and motivation to pupils, students, teachers and other school environments to face the National Science Olympiad, especially mathematics subjects at SMP Negeri 3 Bukittinggi. This training activity was carried out continuously over 3 meetings on 03 June 2023, 05 June 2023 and 09 June 2023. This training activity was carried out using lecture methods, group discussions, games involving 5 mathematics education students. The material presented includes algebra, number theory, geometry and combinatorics. The conclusion is that this activity is able to develop students' learning abilities in solving National Science Olympiad (OSN) questions. This can be seen from the average pretest score which increased from 35.5 to 76.5 when the posttest was held. Kegiatan pelatihan ini bertujuan untuk memberikan semangat dan motivasi kepada mahasiswa, siswa, guru dan lingkungan sekolah lainnya guna menghadapi Olimpiade Sains Nasional khususnya mata pelajaran matematika di SMP Negeri 3 Bukittinggi. Kegiatan pelatihan ini dilakukan secara kontinyu selama 3 kali pertemuan pada tanggal 03 Juni 2023, 05 Juni 2023 dan 09 Juni 2023. Kegiatan pelatihan ini dilaksanakan dengan metode ceramah, diskusi kelompok, permainan yang melibatkan 5 orang mahasiswa pendidikan matematika. Materi yang disampaikan meliputi materi aljabar, teori bilangan, geometri dan kombinatorika